Percutaneous Balloon Retrieval Technique for Fractured Biliary Drainage Catheter in a Paediatric Patient: Can a Major Surgery be Averted? - Amrin Israrahmed; Somesh Singh; Rana Vishwadeep Mall; Rajanikant R Yadav (Journal of Clinical and Diagnostic Research, 2022)
Percutaneous Transhepatic Biliary Drainage (PTBD) involves temporary placement of an external drainage catheter into an obstructed bile duct prior to internal biliary stenting or surgery. Chronic indwelling PTBD catheters can develop surrounding adhesions and are prone to fractures and retention during their removal. Retained segments can cause impaired biliary drainage, inflammation and recurrent cholangitis. Retrieval of retained catheters can be done by endoscopic/surgical/percutaneous techniques. In patients who have undergone Hepatico-Jejunostomy (HJ), endoscopic removal is not possible and percutaneous/surgical removal are the only options. The authors present a case of a five-year-old child who came for removal of a fractured, retained PTBD catheter, nine months after undergoing HJ. The catheter was removed by a percutaneous balloon retrieval technique. The objective here is to highlight the technical challenges encountered and present a modification of the usual balloon retrieval technique used to successfully remove the catheter and thus avert a major surgery.